2018
DOI: 10.1016/j.jmig.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Laparoscopic Abdominal Cerclage Placement During Pregnancy

Abstract: RALAC is a minimally invasive procedure with an acceptable risk profile and comparable efficacy to traditional open abdominal cerclage. RALAC may be considered an acceptable alternative to open abdominal cerclage in pregnancy, and may be a particularly favorable option in certain settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(46 reference statements)
1
6
0
3
Order By: Relevance
“…Literature on robotic TAC is minimal and consists mostly of case reports and series [22]. Gonzales et al report a case series on robotic TAC in pregnancy (11 patients) with 72.7% of deliveries >34 weeks, similar to our outcome of 78.6% of deliveries >34 weeks [7]. There are a number of comparison studies on conventional laparoscopic TAC to laparotomy with results similar to those of our study [8−12].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Literature on robotic TAC is minimal and consists mostly of case reports and series [22]. Gonzales et al report a case series on robotic TAC in pregnancy (11 patients) with 72.7% of deliveries >34 weeks, similar to our outcome of 78.6% of deliveries >34 weeks [7]. There are a number of comparison studies on conventional laparoscopic TAC to laparotomy with results similar to those of our study [8−12].…”
Section: Discussionsupporting
confidence: 84%
“…The robotic-assisted approach to TAC is gaining popularity for reasons related to improved visualization afforded by the 3-dimensional optics and ease of fine dissection and knot tying afforded by the endowristed instruments [7]. Comparison studies exist for conventional laparoscopic TAC vs traditional laparotomy approaches [5,8−13].…”
mentioning
confidence: 99%
“…The systematic search in PubMed and in Scopus databases revealed a total of 42 and 123 search results, respectively, among which 14 studies (four case series and 10 case reports) were identified as eligible for inclusion in this review, according to the inclusion criteria. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] One additional study was identified through the search of references of the included studies. 25 The selected studies for inclusion were presented in details in Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…Perioperative fetal loss is described in four out of 30 cases. The reasons of fetal losses were cardiorespiratory failure and premature rupture of membranes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation